La intriga en los relatos de Ricardo Palma - Chiri Jaime, Sandro (2019)
ResumenLa intriga participa como elemento neurálgico en las tradiciones que Ricardo Palma escribe durante más de medio siglo; vale decir, opera como eje articulador del gran mosaico histórico-ficcional que el escritorperuano se autoimpone como reto artístico personal y como legado a la colectividad de lectores. El presente trabajo rastrea los aportes de Palma en estos temas del arte narrativo.Palabras clave: relato, intriga, Ricardo Palma, tensión, suspense, personajes, ficción. AbstractThe intrigue plays a crucial part in the Traditions that Ricardo Palma writes for over half a century. It functions as an articulating axis of the great historical fictional mosaic that the 19th-century Peruvian writer imposes on himself as a personal and artistic challenge as well as a legacy for his readers. The following work tracks Palma’s contributions in these areas of the art of storytelling.Keywords: story, intrigue, Ricardo Palma, tension, suspense, characters, fiction.